Sustainable Coffee Production through FMEA-FMECA and DMAIC Integration: A Case Study of Pinogu Coffee Producer - Lahay, Idham Halid; Olilingo, Fahrudin Zain (Journal of International Conference Proceedings, 2025)
Sustainable coffee production has become increasingly crucial amid the challenges of climate change and growing consumer demand for eco-friendly products. This study explores the integration of Failure Modes and Effects Analysis (FMEA), Failure Modes, Effects, and Criticality Analysis (FMECA), and the Define, Measure, Analyze, Improve, Control (DMAIC) methodology to enhance sustainability practices at a Pinogu coffee producer. By combining risk identification with data-driven quality improvement, the research provides a comprehensive framework for addressing production inefficiencies and quality issues. The implementation of FMEA-FMECA effectively identified critical failure modes impacting product quality and operational performance, while DMAIC supported continuous improvement through waste reduction and process optimization. The findings demonstrate that aligning risk management tools with quality enhancement strategies offers a viable model for sustainable agricultural practices. This study not only delivers practical guidance for the coffee industry but also contributes valuable insights to the broader discourse on sustainable supply chain management in agribusiness.